Seasonal variations of trace element contents in leaves and bark of horse chestnut (Aesculus hippocastanum L.) in urban and industrial regions in Serbia - Pavlović, Marija; Rakić, Tamara; Pavlović, Dragana; Kostić, Olga; Jarić, Snežana; Mataruga, Zorana; Pavlović, Pavle; Mitrović, Miroslava (Archives of Biological Sciences, 2017)
In this study, we examined the ability of horse chestnut (Aesculus hippocastanum L.) to capture heavy metals, and whether its capacity to absorb metals from soil is associated with surrounding ecological characteristics and sources of pollution. We studied the seasonal accumulation of B, Cu, Sr and Zn in leaves and bark, and the chlorophyll content in the common deciduous tree Aesculus hippocastanum L. in four urban parks in Pančevo, Smederevo, Obrenovac and Belgrade (Serbia) affected by different anthropogenic activities. The research included plants from a control site located within the zone of a former oak forest. Our findings suggest that there are potential ecological risks around Smederevo, Belgrade and Obrenovac due to elevated concentrations of B and Zn relative to the average concentrations described for worldwide soils, as well as national regulations. Substantial and toxic foliar accumulation of B was observed in Smederevo and Belgrade, and of Sr in both plant tissues at all sites. However, the Cu and Zn contents in leaves were not enough to meet the physiological needs of plants. Chlorophyll a and the total carotenoid content peaked in August under the most unfavorable conditions of the year, which may be considered as an adaptive mechanism. The obtained results showed the remarkable complexity of environmental conditions and the difficulties A. hippocastanum, as a species, has to overcome. Under conditions of different types of urban and industrial pollution, A. hippocastanum showed great element accumulation potential and could be regarded as both an accumulator and a response indicator, since its leaves are quite susceptible to damage. https://doi.org/10.2298/ABS161202005P Received: December 2, 2016; Revised: January 12, 2017; Accepted: January 31, 2017; Published online: February 2, 2017 How to cite this article: Pavlović M, RakićT, PavlovićD, Kostić O, Jarić S, Mataruga Z, Pavlović P, Mitrović M. Seasonal variations of trace element contents in leaves and bark of horse chestnut (Aesculus hippocastanum L.) in urban and industrial regions in Serbia. Arch Biol Sci. 2017;69(2):201-14.